Peran Guru Kelas Dalam Pelaksanaan Bimbingan dan Konseling di SDN Serang 03 - Rahmah, Ratu Hety Novia; Chudari, Ima Ni'mah (Didaktika, 2021)
In elementary school guidance and counseling are not handled specifically by counsellors or teachers BK. In order to perform this role, the class teacher must pay attention to the level of development of each student. The purpose of this research is to find out about the role of classroom teachers in the implementation of guidance and counseling, the implementation of guidance and counseling at SDN Serang 03, and the obstacles faced by classroom teachers in the implementation of guidance and counseling at SDN Serang 03. This study uses qualitative approach combined with case study method. The subjects of the study were grade II teachers, grade V teachers, and principals of SDN Serang 03. Researchers use data collection techniques in the form of interviews, observations and documentation. In analyzing the data, researchers conducted data reduction activities, data presentation, and conclusion drawing. The results of the study conducted by researchers showed that the role of classroom teachers in the implementation of guidance and counseling at SDN Serang 03 has been implemented well although there are some aspects that have not been achieved optimally due to the covid-19 pandemic. At SDN Serang 03, the role of classroom teachers in the implementation of guidance and counseling is inseparable from collaboration with parents in providing guidance to students. The conclusion of this study is the role of class teachers in the implementation of guidance and counseling is indispensable to help the development of learners.